2022
DOI: 10.3389/fcell.2022.1075233
|View full text |Cite
|
Sign up to set email alerts
|

Adipose tissue-derived small extracellular vesicles modulate macrophages to improve the homing of adipocyte precursors and endothelial cells in adipose tissue regeneration

Abstract: Rapid infiltration of endogenous cells induced by cell-free biomaterials is the first and crucial step in tissue regeneration and macrophage is largely involved. Our previous study reported adipose tissue-derived small extracellular vesicles (sEV-AT) could successfully promote adipose tissue regeneration. However, the role of macrophages in this process was unknown. In this study, we isolated sEV-AT and subcutaneously implanted it into the back of SD rats. The results showed sEV-AT increased macrophage infiltr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…However, cellular therapies have been restricted by factors such as necrosis, immune rejection, ethical issues, and tumor risk. Small extracellular vesicles, also known as exosomes, as the research hotspot of cell-free tissue engineering in the past years 28 and have been used for skin wound repair. [29][30][31][32] However, recent studies have shown that apoptosis occurred soon after cell transplantation, 7 so apoptotic extracellular vesicles (ApoEVs) were more likely to play a regulatory role than exosomes.…”
Section: Discussionmentioning
confidence: 99%
“…However, cellular therapies have been restricted by factors such as necrosis, immune rejection, ethical issues, and tumor risk. Small extracellular vesicles, also known as exosomes, as the research hotspot of cell-free tissue engineering in the past years 28 and have been used for skin wound repair. [29][30][31][32] However, recent studies have shown that apoptosis occurred soon after cell transplantation, 7 so apoptotic extracellular vesicles (ApoEVs) were more likely to play a regulatory role than exosomes.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that due to the differences in density among different tissues, attention must be paid when applying the above conclusions to other tissues. Most EVs isolated from adipose tissue have used tissue culture methods to process the tissue (Kranendonk et al 2014a , b ; Huang et al 2021 ; Dong et al 2022 ; Hong et al 2022 ). When extracting EVs from the brain, enzymatic digestion methods are used more frequently, partly because brain samples are cryopreserved and are not suitable for tissue culture methods (Perez-Gonzalez et al 2012 ; Muraoka et al 2020a , b ; Su et al 2021 ).…”
Section: Tissue Processingmentioning
confidence: 99%
“…Adipose Ti-EVs play an critical role in the progression of obesity and insulin resistance, as well as some obesity-related metabolic diseases (Jayabalan et al 2019 ; Camino et al 2020 ). They can also promote wound re-epithelialization, granulation tissue formation, and hair follicle regeneration, thereby accelerating skin wound healing (Dai et al 2017 ; Dong et al 2020 , 2022 ; Pan et al 2023 ). More studies pay their attention on the role of Ti-EVs in tumors, and they have been shown to involve in various processes of tumorigenesis and progression.…”
Section: Introductionmentioning
confidence: 99%
“…[ 40 , 41 ] In response to injury, endogenous cells migrate to the damaged area under the guidance of microenvironmental chemokines and growth factors such as vascular endothelial growth factor (VEGF), platelet derived growth factor (PDGF), tumor necrosis factor alpha (TNF‐α), fibroblast growth factor (FGF), and insulin‐like growth factor 1 (IGF‐1) thus contributing to the repair and regeneration of tissues such as uterus. [ 42 , 43 , 44 , 45 , 46 ] Therefore, the recruitment of endogenous cells, and the provision of in situ regenerative treatments present a promising therapeutic approach for the repair of the endometrium. [ 47 ] Considering these factors, it is important to design and construct an ECM material that precisely localizes within the endometrium and releases bioactive substances continuously to facilitate endometrial restoration and regeneration.…”
Section: Introductionmentioning
confidence: 99%